2016
DOI: 10.1021/acs.jpcc.6b01868
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Water-Soluble WS2 Quantum Dots for Turn-On Fluorescent Measurement of Lipoic Acid

Abstract: A facile and eco-friendly approach for the synthesis of water-soluble WS2 quantum dots (QDs) was developed via ultrasonication and a hydrothermal process from bulk WS2. In this strategy, the dispersity of bulk WS2 in aqueous phase was improved with the aid of a surfactant (hexadecyltrimethylammonium bromide, CTAB), which could shorten the exfoliation time and improve the exfoliation efficiency to form layered WS2 nanosheets. Through hydrothermal treatment, the nanosheets were further scissored into QDs with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 70 publications
5
92
0
Order By: Relevance
“…The QY of MoS 2 quantum dots is reported from 2.6% to 4.84% (Wu et al, 2015;Wang and Ni, 2014) and the QY of WS 2 quantum dots is reported from 1.8% to 4% Yan et al, 2016). The MoS 2 and WS 2 quantum dots also shows excitation-dependent emission.…”
Section: Comparison Of Graphene and Graphene-like 2d Materails As Donorsmentioning
confidence: 93%
“…The QY of MoS 2 quantum dots is reported from 2.6% to 4.84% (Wu et al, 2015;Wang and Ni, 2014) and the QY of WS 2 quantum dots is reported from 1.8% to 4% Yan et al, 2016). The MoS 2 and WS 2 quantum dots also shows excitation-dependent emission.…”
Section: Comparison Of Graphene and Graphene-like 2d Materails As Donorsmentioning
confidence: 93%
“…Wang's group adopted liquid alloy‐assisted intercalation and exfoliation method to prepare MoS 2 QDs and WS 2 QDs. In this article, bulk TMDs powder were firstly saturated with liquid alkali metal sodium and potassium alloy, and subsequently, QDs were obtained through the reaction between alkali metals and water …”
Section: Synthesismentioning
confidence: 99%
“…In addition to the ultrasonic treatment, the high dispersibility supported by suitable solvents was also essential in the 0D TMDs preparation. So far, those researched solvents can be classified as water phase (e.g., sulfuric acid, surfactants aqueous solution), and organic solvents phase (e.g., N, N‐dimethylformamide (DMF), N‐methyl‐2‐pyrrolidone (NMP), isopropyl alcohol (IPA), and ethylene glycol) . For example, a sulfuric acid‐assisted ultrasonic route was provided for controllable‐size MoS 2 QDs with excellent PL properties through exfoliating and cutting bulk MoS 2 powder .…”
Section: Synthesismentioning
confidence: 99%
“…Although chemical vapor deposition and mechanical exfoliation lead to large-area layers, sonication solvent-based exfoliation is a convenient method to realize mono-and few-layer flakes. [6] In a recent work, researchers have demonstrated a unique piezoelectric behavior of noncentrosymmetric-layered structures as MoS 2 which opens a new pathway toward the high-performance exfoliation of such TMD materials. While water molecules weaken the Van der Waals force between the stacked layers, DMSO molecules facilitate the exfoliation process.…”
mentioning
confidence: 99%
“…While graphene possesses a zero bandgap at its Dirac point, many TMDs exhibit a transformation from an indirect bandgap in bulk to a direct bandgap in a single layer, which leads to strong photoluminescence (PL) of TMD single layers. [6] In a recent work, researchers have demonstrated a unique piezoelectric behavior of noncentrosymmetric-layered structures as MoS 2 which opens a new pathway toward the high-performance exfoliation of such TMD materials. Among various TMDs, Tungsten disulfide (WS 2 ) is one of the components that has a lot of excellent electrical properties.…”
mentioning
confidence: 99%